GHSR DNA hypermethylation is a common epigenetic alteration of high diagnostic value in a broad spectrum of cancers - Moskalev, Evgeny A.; Jandaghi, Pouria; Fallah, Mahdi; Manoochehri, Mehdi; Botla, Sandeep K.; Kolychev, Oleg V.; Nikitin, Evgeny A.; Bubnov, Vladymyr V.; Doeberitz, M. Von Knebel; Strobel, Oliver; Hackert, Thilo; Buechler, Markus W.; et al. (Oncotarget, 2015)
Identification of a single molecular trait that is determinant of common malignancies may serve as a powerful diagnostic supplement to cancer type-specific markers. Here, we report a DNA methylation mark that is characteristic of seven studied malignancies, namely cancers of lung, breast, prostate, pancreas, colorectum, glioblastoma and B cell chronic lymphocytic leukaemia (CLL) (n = 137). This mark was defined by substantial hypermethylation at the promoter and first exon of growth hormone secretagouge receptor (GHSR) through bisulfite pyrosequencing. The degree of aberrant methylation was capable of accurate discrimination between cancer and control samples. The highest sensitivity and specificity of cancer detection was achieved for cancers of pancreas, lung, breast and CLL yielding the area under the curve (AUC) values of 1.0000, 0.9952, 0.9800 and 0.9400, respectively. Narrowing to a single CpG site within the gene's promoter or four consecutive CpG units of the highest methylation levels within the first exon improved the detection power. GHSR hypermethylation was detected already at the early stage tumors. The accurate performance of this marker was further replicated in an independent set of pancreatic cancer and control samples (n = 78). These findings support the candidature of GHSR methylation as a highly accurate pan-cancer marker.
EVALuna2:6727